2018
DOI: 10.1080/14786419.2018.1536659
|View full text |Cite
|
Sign up to set email alerts
|

Chemical composition of essential oils from different parts of Protium heptaphyllum (Aubl.) Marchand and their in vitro antibacterial activity

Abstract: In Brazilian folk medicine, Protium heptaphyllum is used to treat inflammatory conditions and to hasten wound repair. This paper aims to investigate the chemical composition and the in vitro antibacterial effects of the essential oils (EOs) obtained from P. heptaphyllum leaves and ripe and unripe fruits against a representative panel of oral pathogens. The GC-FID and GC-MS analysis revealed that the major components determined in P. heptaphyllum essential oils were myrcene (59.0%), β-elemene (17.2%), limonene … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 26 publications
0
5
0
5
Order By: Relevance
“…Although antibacterial activity has previously been described in B. crassifolia, Pro. heptaphyllum, and Xylopia aromatica [20][21][22][23][24], we found that only some of the plant part extracts inhibited both M. tuberculosis growth and the kinase activity. e flower extract of B. crassifolia had an IC 50 of 30.4 μg/ml and an MIC of 500 μg/ml, while the inner bark extract showed an IC 50 of 144 μg/ml but an MIC higher than 500 μg/ml.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…Although antibacterial activity has previously been described in B. crassifolia, Pro. heptaphyllum, and Xylopia aromatica [20][21][22][23][24], we found that only some of the plant part extracts inhibited both M. tuberculosis growth and the kinase activity. e flower extract of B. crassifolia had an IC 50 of 30.4 μg/ml and an MIC of 500 μg/ml, while the inner bark extract showed an IC 50 of 144 μg/ml but an MIC higher than 500 μg/ml.…”
Section: Discussionmentioning
confidence: 73%
“…Phytochemical studies of the essential oils of X. aromatica and Prot. heptaphyllum leaves demonstrated the presence of various terpenes, including spathulenol [ 20 , 21 ]. This sesquiterpene has been shown to have antibacterial activity against Cryptococcus neoformans , Enterococcus faecalis , and Staphylococcus aureus [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several essential oil compounds have high potential on antibacterial activity and these compounds are monoterpenic, sesquiterpenic and phenylpropanoid with proven action as limonene (Goulart et al, 2018), thymol (Majolo et al, 2020), germacrene D (Freitas et al, 2020), caryophyllene and α-pinene (Nelson, 2019), β-bisabolene (Mazaheritehrani et al, 2021) and myrcene (Cabral et al, 2020). The cytotoxic assay on A. salina showed LC 50 = 90.17 ± 1.90b and 625.08 ± 2.88c µg mL -1 for the essential oil of fresh leaves and xylopodium of C. regium.…”
Section: Resultsmentioning
confidence: 99%
“…However, the mechanisms involved in the observed anti-inflammatory action were not clarified. More recently, antibacterial activity [36][37][38] and effects on blood sugar level and lipid profile have also been highlighted for the essential oil obtained from P. heptaphyllum gum resin [39][40][41]. The observed effects on lipid metabolism involved a decrease of total cholesterol, LDL-C, serum triglycerides, and VLDL, with an elevation of high-density lipoprotein cholesterol (HDL-C).…”
Section: Introductionmentioning
confidence: 99%